1992
DOI: 10.1016/s0022-5347(17)37026-x
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 in Renal Cell Carcinoma

Abstract: We studied interleukin-6 production in 4 human renal cell carcinoma cell lines and measured the serum level in 71 patients with renal cell carcinoma, thus, clarifying a relationship between interleukin-6 secretion and an occurrence of the paraneoplastic syndrome in the carcinoma. Interleukin-6 was produced by 3 cell lines and detected in 25% of the patients. The level of interleukin-6 did not directly correlate with tumor volume and the differentiation grade of the carcinoma. However, the positive rate increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
1
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(50 citation statements)
references
References 15 publications
1
47
1
1
Order By: Relevance
“…Increased serum levels of IL-6, found in a large percentage of patients, correlated with tumor size and grade, and IL-6 pretreatment serum levels correlated as an independent factor with prognosis, similarly as in many solid tumors, including renal cancer, 52 colorectal cancer, 19,53 lung cancer, 54 gynecological cancers 55 and melanoma. 25 Tamm et al have shown that IL-6 may directly promote tumor cells motility and invasion.…”
Section: Cytokine Serum Levels During Follow-upmentioning
confidence: 85%
“…Increased serum levels of IL-6, found in a large percentage of patients, correlated with tumor size and grade, and IL-6 pretreatment serum levels correlated as an independent factor with prognosis, similarly as in many solid tumors, including renal cancer, 52 colorectal cancer, 19,53 lung cancer, 54 gynecological cancers 55 and melanoma. 25 Tamm et al have shown that IL-6 may directly promote tumor cells motility and invasion.…”
Section: Cytokine Serum Levels During Follow-upmentioning
confidence: 85%
“…Blay et al (1992) reported that serum IL-6 was positive in 48% of patients with RCC. Tsukamoto et al (1992) reported that it was positive in 25% and Hamao et al (1994) reported that it was positive in 53%. In our study, serum IL-6 could be detected in all patients in the control group and RCC group by using a highly sensitive ELISA kit in our present study.…”
Section: Discussionmentioning
confidence: 99%
“…They also reported that the presence of high pretreatment serum IL-6 levels inversely correlated to the response to IL-2 and to survival after immunotherapy with IL-2 in patients with RCC (Blay et al, 1990). Tsukamoto et al (1992) reported that serum IL-6 was detected in 18 out of 71 patients (25%). They indicated that although IL-6 level did not directly correlate with tumour volume and differentiation grade of the carcinoma, the positive rate increased with progression of the stage, and that serum IL-6 level affected the 5-year survival of patients without distant metastasis.…”
mentioning
confidence: 99%
“…IL-6 is also reported to be produced by other epithelial tumors [5]. Increased serum IL-6 levels have been found in patients with multiple myeloma [6], renal cell carcinoma [7], bladder carcinoma [8], head and neck cancer [9], ovarian cancer [10], and cholangiocarcinoma [11].…”
Section: Introductionmentioning
confidence: 99%